2015
DOI: 10.1093/ecco-jcc/jjv175
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes in Steroid-refractory Ulcerative Colitis Treated with Tacrolimus Alone or in Combination with Purine Analogues

Abstract: Our study supports the efficacy of tacrolimus in steroid-refractory UC. Purine analogues appear to be beneficial for the long-term outcome of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…The long‐term safety and efficacy of tacrolimus could not be evaluated in this study. Several retrospective studies suggest that long‐term tacrolimus therapy is safe and effective in refractory IBD . Nevertheless, RCTs are necessary to rigorously assess the safety and efficacy of tacrolimus as maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long‐term safety and efficacy of tacrolimus could not be evaluated in this study. Several retrospective studies suggest that long‐term tacrolimus therapy is safe and effective in refractory IBD . Nevertheless, RCTs are necessary to rigorously assess the safety and efficacy of tacrolimus as maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that tacrolimus is useful as an alternative option for steroid‐refractory UC. Furthermore, a recent study reported that tacrolimus was useful for the long‐term management of steroid‐refractory UC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in UC have reported the possible benefit of combining thiopurines with tacrolimus, as purine analogues were shown to be associated with a higher rate of clinical remission and longer time to colectomy. 25 Nevertheless, these factors have not been previously described in patients with CD. Importantly, the relationship between blood drug concentrations during induction and clinical disease activity are relevant findings that may help to increase the likelihood of response in these cases.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…[52][53][54][55] Like patients treated with CsA, steroid-refractory UC patients who achieve remission with TAC treatment would require immunomodulators to maintain remission and prevent colectomy. Recently, Schmidt et al 56 reported the effect of purine analogs (PAs) on the long-term clinical outcomes of 156 moderately to severely active steroid-refractory UC patients treated with TAC. The Kaplan-Meier curve for colectomy-free survival after month 3 showed a benefit in the PA group.…”
Section: ) Cyclosporine Amentioning
confidence: 99%